Terreno vigilante: compreendendo as ações dos jovens com uma missão (JOCUM) em Juazeiro do Norte-CE - Meneses, Itamara Freires de (2016)
This paper aims to analyze the missionary activities carried out by "Youth With A Mission" (YWAM) in the city of North- EC of Juazeiro, in the context of the Pilgrimage of All Souls. It started from the hypothesis that YWAM, represented by a faction of Pentecostalism and "foreign" to local traditions, is an alternative in achieving a larger space in the religious goods and services market in the conversion of the faithful process a reality that appears largely Catholic. For this time, the following procedures were used: literature and field research, participant observation with an ethnographic approach, semi-structured interviews with the group members and photographic records. This is an important methodological framework for understanding the nuances and possibilities of complex societies in a propositional attitude and ethics (VELHO, 1994).